Refleksi Perataan Laba terhadap Respon Pasar - Paramita, Ratna Wijayanti Daniar (Jurusan Akuntansi Politeknik Negeri Malang, 2017)
AbstractThe purpose of this study is to obtain empirical evidence, examine and explain the effect of companies that implement income smoothing towards the market response, with voluntary disclosure as moderating variables. This study uses the secondary data of 143 manufacturing companies that go public in BEI (Indonesian Stock Exchange) during 2011-2015. This research variables include income smoothing as an independent variable, the market response is proxies by Earnings Response Coefficient (ERC) as the dependent variable and voluntary disclosure is moderating variable. The data analysis methods is regression with single moderating variable. The study finds that income smoothing affects the market response both individually and partially. The results also reveal that earnings information delivered on the date of the announcement was responded positively by investors. However, the presentation of the full report in the form of voluntary disclosure actually reduces the market response to earnings at the date of announcement.AbstrakTujuan penelitian ini adalah untuk memperoleh bukti empirik, menguji dan menjelaskan pengaruh perusahaan yang melakukan income smoothing terhadap respon pasar dengan voluntary disclosure sebagai variabel pemoderasi pada perusahaan manufaktur yang go public di BEI tahun 2011-2015 sebanyak 143 perusahaan. Variable penelitian ini income smoothing sebagai variabel bebas, respon pasar diproksikan dengan Earnings Response Coefficient (ERC) sebagai variabel terikat dan voluntary disclosure adalah variabel moderasi. Metode analisis data menggunakan regresi dengan variabel moderasi tunggal. Income smoothing secara individu dan parsial berpengaruh terhadap respon pasar. Laba yang disampaikan pada tanggal pengumuman direspon positif oleh investor. Namun demikian penyajian laporan secara lengkap dalam bentuk voluntary disclosure justru mengurangi respon pasar terhadap laba pada tanggal pengumuman.